Taxonomy and Broad-Spectrum Antifungal Activity of Streptomyces sp. SCA3-4 Isolated From Rhizosphere Soil of Opuntia stricta - Qi, Dengfeng; Zou, Liangping; Zhou, Dengbo; Chen, Yufeng; Gao, Zhufen; Feng, Renjun; Zhang, Miaoyi; Li, Kan; Xie, Jianghui; Wang, Wei (Frontiers in Microbiology, 2019)
Actinomycetes are important producers of antibiotics and other important bioactive substances. Extraordinary ecosystems cause the evolution of novel secondary metabolic pathways of Actinomycetes, and increase the discovery possibility of new biological functions of bioactive compounds. Here, we isolated a rare Actinomycete from the soil samples of Cactus rhizosphere. An antagonistic Actinomycete strain (named SCA3-4) was screened against Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4, ATCC 76255). The strain produced Pink-white aerial mycelia and brown substrate mycelium on gause No. 1 agar. Biverticillate chains of cylindrical spores were detected by scanning electron microscope (SEC). Analysis of the 16S rRNA sequence and a phylogenetic tree exhibited that the SCA3-4 strain shared a 99.54% similarity with Streptoverticillium lilacinum NRRL B-1968T and clustered into the same branch. Based on morphological, biochemical, physiological and molecular characteristics, the SCA3-4 strain was identified as Streptoverticillium sp. It can grow well on the different antibiotic medium with chloramphenicol, streptomycin, penicilin-G, gentamicin, erythromycin or neomycin sulfate. The PCR amplification of type I and Ⅱ polyketide synthase genes (PKS-I and PKS-Ⅱ) supported that the SCA3-4 strain owned the possible antimicrobial activity. Ethyl acetate extracts of the SCA3-4 strain showed a broad-spectrum antifungal activity against 13 plant pathogenic fungi including Foc TR4 and F. oxysporum f. sp. Cubense race 1 (ACCC 31271). The results of transmission electron microscope (TEM) showed that the crude extracts at the concentration 100 μg/ml inhibited spore germination and growth of Foc TR4 fungal spores by destroying cell membrane. 21 different compounds were identified from ethyl acetate extract of SCA3-4 strain by Gas Chromatography-Mass Spectrometry (GC-MS). These compounds were comprised of phenolic compound, pyrrolizidine, hydrocarbons, esters, and acids. Some compounds were already reported to possess antimicrobial or other biological activities. Other compounds with no functional annotation will be paid more and more attention to the discovery of new bioactive substances in the future.